Dynamic Programming and Bayesian Inference Concepts and Applications - Saber Fallah Nezhad, Mohammad (IntechOpen, 2014)
Dynamic programming and Bayesian inference have been both intensively and extensively developed during recent years. Because of these developments, interest in dynamic programming and Bayesian inference and their applications has greatly increased at all mathematical levels. The purpose of this book is to provide some applications of Bayesian optimization and dynamic programming.